Massager-stimulator application in rehabilitation for musculoskeletal system diseases - A. D. Chuvashova (Лечащий Врач, 2024)
Background. Back pain is one of the most common complaints of patients. There are a large number of causes of pain syndrome. This article emphasizes on the traumatism of athletes and the importance of timely and effective rehabilitation measures that can improve the quality of life. Undoubtedly, the role of exercise in the prevention of musculoskeletal diseases is great. In addition, physical exercise is included in the list of recommendations for their prevention and treatment. But, on the other hand, increased physical activity can have a negative impact on the condition of the joints and spine. A vivid example of this is the prevalence of pain syndrome in various parts of the spine in athletes. Various factors can cause degenerative and dystrophic processes in the spine. First, changes occur in the intervertebral discs – they lose elasticity and elasticity, their shock absorption decreases. Then the changes spread to the rest of the spinal tissues. It is generally believed that age is one of the main factors provoking pathological processes in the spine and musculoskeletal system as a whole. But it is impossible not to mention other reasons, which are no less provoking the development of degenerative-dystrophic changes. One of them is physical exertion that exceeds the body's capabilities. As a result, there are often stretched ligaments or traumatization of muscles. Other causes of pain syndrome in athletes include: spondylolysis – defect of the vertebral arch, spondylolisthesis – displacement of one vertebra in relation to another, spondyloarthrosis – degenerative-dystrophic disease of spinal joints and so on.Conclusion. The earlier the appropriate treatment is carried out, the lower the probability of chronicization of the pain syndrome and complications of the situation. Treatment of low back pain in athletes is aimed not only at managing the pain syndrome, but also at eliminating the provoking factor, restoring mobility, stability and supportability of the spine through competent and timely rehabilitation measures.